Effect of trawling on dietary patterns of demersal fish community along the - Asha Nair, M; Aravindan, C M (Indian Journal of Fisheries, 2011)
The pattern of trophic organizations within fish community reflect the food resource partitioning existing in a given marineecosystem. The present investigation was undertaken to understand the shifts in the dietary pattern of three demersal finfishspecies at two different sites, one where intense trawling is practised and the other where no trawling is undertaken. Multivariatestatistical analysisviz., cluster analysis was carried out to understand these patterns. Results of the study revealed interestingdiet sharing patterns among the selected demersal fishes at trawled and non-trawled sites.